Social media impact on traditional media: a review on the reason behind the closure of Utusan Malaysia - Kobiruzzaman, M. M.; Ahmad Ghazali, Akmar Hayati (Research Publishing Academy, 2022)
Social media has changed people's behaviour, attitudes, habits, lifestyles, and the process of communication. The scholar describes social media as a double-edged sword because of having a positive and negative impact on society. The aim of the paper is to identify the effects of social media on traditional media, especially on printed newspapers. Content analysis in systematic reviews has been applied to collect data from secondary sources such as journal articles, newspaper articles, government websites, and nongovernment websites. Based on the collected data, social media's positive effects on society are imparting knowledge, accelerating the communication process, building a virtual workplace, and e-commerce marketing. On the other hand, social media's adverse effects are cyberbullying, hacking, addiction, and spreading fake news. Social media have threatened the printed newspaper, and the journalist confronts challenges staying on track. The circulation of the daily printed newspaper declined gradually due to the revolution of social media and social media-based citizen journalism practising in Malaysia. Many newspapers have been compelled to cease their operation due to losing subscribers dramatically. Finally, this paper provides a review of the reason behind the closure of printed newspapers in Malaysia. Based on the discussions and the previous study, the paper presents three significant reasons behind Utusan Malaysia's closure: poor economic conditions, political crisis, social media revolution, and citizen journalism practising in Malaysia. In conclusion, few suggestions have been discussed that might help printed newspapers in Malaysia to survive in the digital era.